2015
DOI: 10.1111/joor.12354
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of the calcification of the nuchal ligament and osteophytes of the cervical spine in obstructive sleep apnoea subjects and snorers

Abstract: The previous reports suggest that obstructive sleep apnoea (OSA) is related to metabolic syndrome, mineral metabolism disorders and cardiovascular disease. In addition, a possible relationship between obesity and the calcification of ligaments has been implied. However, the potential link between OSA and the calcification of ligaments has not been directly studied. In this present study, to investigate the potential link between OSA and the calcification of ligaments, we examined the prevalence of the calcific… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 22 publications
0
2
0
Order By: Relevance
“…In addition, there are several case reports which regard OSA patients with cervical spinal osteophytes, as one of the causes of airway obstruction [8,9]. [2] In a previous study to investigate the potential link between OSA and the calcification of ligaments, the prevalence of the calcification of ligaments in OSA patients and the relationship between these findings, and OSA severity were examined [10]. They reported that there was a significant positive correlation between the severity of OSA and the calcification of the nuchal ligament, before and after, adjusting for BMI.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, there are several case reports which regard OSA patients with cervical spinal osteophytes, as one of the causes of airway obstruction [8,9]. [2] In a previous study to investigate the potential link between OSA and the calcification of ligaments, the prevalence of the calcification of ligaments in OSA patients and the relationship between these findings, and OSA severity were examined [10]. They reported that there was a significant positive correlation between the severity of OSA and the calcification of the nuchal ligament, before and after, adjusting for BMI.…”
Section: Introductionmentioning
confidence: 99%
“…OSAS causes an abnormal opening of the mouth during the night, with a structural and functional alteration of the neck; there is a close relationship between this syndrome and the decrease in hearing 8,9…”
mentioning
confidence: 99%